Effects of the use of N95 Mask on Oxygen Saturation, Hemodynamic Status and Physical Performance of Nurses - Lousiana, Maria; Natalia, Lia; Sulismawarti, Diah Suryani; Amalia, Ruli (Indonesian Journal of Global Health Research, 2024)
COVID-19 was an emerging disease that can be transmitted rapidly via droplets and aerosols with a high mortality rate. During pandemic, nurses had a high risk of contracting COVID-19 so efforts to prevent transmission need to be made by using personal protective equipment (PPE). N95 masks were the standard personal protective equipment recommended by WHO, however wearing N95 masks for a long period of time can cause physiological stress, namely breathing, body heat balance, vision, communication, feeling comfortable, difficulty eating and sneezing as well as other PPE worn. This study aimed to identify the effect of using N95 masks on oxygen saturation, hemodynamic status and physical performance in nurses at X Hospital. The research method used was a pre-experimental design, one group pre and post test, including one intervention group that measured lung function and physical performance. The sampling technique in this research was non-probability sampling with purposive sampling of 94 respondents. Respondents underwent a pretest, then lung function and physical performance were examined after 4 hours of using an N95 mask. The results of data analysis using the Wilxocon test showed that there were differences in oxygen saturation (p-value = 0.000), hemodynamic status such as respiratory frequency (p-value = 0.000), systolic blood pressure (p-value = 0.012) and pulse frequency (p- value = 0.000), as well as the physical performance of nurses (p-value = 0.000) before and after using the N95 mask. The results of this research can contribute to standardizing the use of PPE and preventing complications due to changes in oxygen saturation and hemodynamic status so that nurses physical performance improves.